Adapting urban best management practices for resilience to long‐term environmental changes. (20th July 2020) - Job, Scott C.; Harris, Maureen; Julius, Susan; Butcher, Jonathan B.; Kennedy, Joseph Todd
Abstract: Stormwater best management practices (BMPs) help mitigate the adverse effects of urban development on stream hydrology and water quality, and are widely specified in development requirements and watershed management plans. However, design of stormwater BMPs largely relies on experience with historic climate, which may not be a reliable guide to the future. To inform BMP design that is robust to future conditions, it is important to examine how potential changes in precipitation, temperature, and potential evapotranspiration will affect the performance of BMPs. We use continuous simulation modeling to examine BMP performance under current and potential future climatic conditions and determine the changes needed in site configuration to address future impacts. We perform modeling for five development types in five different regions of the United States and explore both conventional ("gray") and green infrastructure (GI) stormwater management approaches. If stormwater designs are adapted to address potential future climate conditions, this study suggests that the most cost‐effective approaches may use both gray and green BMPs. If the magnitude of extreme weather events increases dramatically, then gray practices that provide detention storage may have better cost‐effectiveness. Incorporating risk of future climate impacts into stormwater design may help communities become more resilient. Practitioner points: There is a risk that projected changes in meteorological forcing will negatively affect stormwater BMP performance. Under projected future climate conditions, this study suggests the most cost‐effective approaches may use both gray and green BMPs. If the magnitude of extreme weather events increases dramatically, gray practices that provide detention storage may have better cost‐effectiveness. Flexibility is beneficial in adaptation and resilience planning due to uncertainty in projected precipitation volume and intensity changes. Abstract : We use continuous simulation modeling to examine stormwater best management practice performance under current and potential future climatic conditions and determine the changes needed in site configuration to address future impacts.